Implementasi Perda No. 07 Tahun 2013 tentang Pengelolaan Sampah di Kabupaten Badung - Novitayanti, Anak Agung Dwi; Erviantono, Tedi; Mahaswari Jayanthi Mertha, Anak Agung Sagung Mirah (Jurnal Nawala Politika, 2022)
This research analyzes how the implementation of Regional Regulation No. 07 of 2013 on Waste Management in Badung Regency, with the problem of unoptimal in realizing waste management regulation No. 07 of 2013. Research objectives include: (1). Tracing the socio-political conditions of content and the context of the implementation of waste management policy no. 07 of 2013 in Badung Regency, (2). Know the role of local actors in the development of their own territory. The theory used is the theory of the implementation of merille S. Grindle's policy. The study used a qualitative descriptive approach in obtaining data.